225k views
1 vote
Express b+1/3b-2 with “b” as the subject

Express b+1/3b-2 with “b” as the subject-example-1

2 Answers

4 votes

Answer:


→a = ((b + 1))/((3b - 2)) \\ a(3b - 2) = (b + 1) \\ 3ab - 2a = b + 1 \\ 3ab - b = 2a + 1 \\ b(3a - 1) =( 2a + 1) \\ \boxed{b = ((2a + 1))/((3a - 1)) }✓

  • b = (2a+1)/(3a-1) is the right answer.
5 votes

Answer:

b =
(1+2a)/(3a-1)

Explanation:

Given

a =
(b+1)/(3b-2) ( multiply both sides by 3b - 2 )

a(3b - 2) = b + 1 ← distribute left side

3ab - 2a = b + 1 ( subtract b from both sides )

3ab - b - 2a = 1 ( add 2a to both sides )

3ab - b = 1 + 2a ← factor out b from each term on the left side

b(3a - 1) = 1 + 2a ( divide both sides by 3a - 1 )

b =
(1+2a)/(3a-1)

User Meyumer
by
6.1k points